Financial Innovation, Sustainable Economic Growth, and Credit Risk: A Case of the ASEAN Banking Sector - Khan, Ali Burhan; Fareed, Muhammad; Salameh, Anas A.; Hussain, Haroon (Frontiers in Environmental Science, 2021)
A dynamic and rapidly changing global financial environment is posing various risks for the banking sector. Therefore, the future of the Association of Southeast Asian Nations (ASEAN) banks depends on how efficiently and effectively they manage these risks. Among these risks, a credit risk is the most crucial risk for the banking sector. Thus, the current study aims to analyze the impact of financial innovation and sustainable economic growth on the credit risk of ASEAN banks. For this purpose, a sample of 4 ASEAN countries from 2011 to 2018 is selected, and by applying a panel-corrected standard error (PCSE) approach, both variables were found to be a significant contributor toward the credit risk. Current research will not only be beneficial for the management of ASEAN countries’ banks but also provide help to the overall financial industry and their respective regulatory bodies to understand the behavior of ASEAN banks’ credit risk regarding financial innovation and economic growth. Thus, this study will play an essential role concerning the stability of the banking sector in the ASEAN region.